Green Tea Intake and Risks for Dementia, Alzheimer’s Disease, Mild Cognitive Impairment, and Cognitive Impairment: A Systematic Review - Kakutani, Saki (Nutrients, 2019)
Dementia has become a major issue that requires urgent measures. The prevention of dementia may be influenced by dietary factors. We focused on green tea and performed a systematic review of observational studies that examined the association between green tea intake and dementia, Alzheimer’s disease, mild cognitive impairment, or cognitive impairment. We searched for articles registered up to 23 August 2018, in the PubMed database and then for references of original articles or reviews that examined tea and cognition. Subsequently, the extracted articles were examined regarding whether they included original data assessing an association of green tea intake and dementia, Alzheimer’s disease, mild cognitive impairment, or cognitive impairment. Finally, we included three cohort studies and five cross-sectional studies. One cohort study and three cross-sectional studies supported the positive effects of green tea intake. One cohort study and one cross-sectional study reported partial positive effects. The remaining one cohort study and one cross-sectional study showed no significant association of green tea intake. These results seem to support the hypothesis that green tea intake might reduce the risk for dementia, Alzheimer’s disease, mild cognitive impairment, or cognitive impairment. Further results from well-designed and well-conducted cohort studies are required to derive robust evidence.